(untitled) (Journal of Economic Research & Business Administration, 2018)
The investment cooperation between Kazakhstan and China provides the results for interacting parties. For Kazakhstan, the result of investment cooperation with China should contribute to a continuing sustainable economic growth, modernization of the domestic economy with the participation in the system of world relations, for China it is a solution to the problem of preservation of sustainable economic development.For China, investment and economic cooperation in the project “One Let us explain one way” identifies opportunities in expanding markets, the further development of export potential. Securing the position of China in Kazakhstan’s economy – the broadening and deepening of trade and economic cooperation within the economic zone of New Silk Road.The existing commodity structure of imports determined the unrealized potential for strengthening relations with countries, consisting in the development of machine-building, chemical, agro-industrial complexes, and the food industry. The economy of most countries of the Silk Road has a commodity orientation and to achieve the goal of increasing the competitiveness of national economies, strengthening the position in the international division of labor, they should gradually change their specialization towards intercountry cooperation, orient the economy towards innovation development, and implement interstate innovative projects. The development of transport and logistics services, the creation of modern transport corridors will significantly reduce the time of transportation of raw materials, semi-finished products and finished products, reduce transport costs, lead to a reduction in production costs and will affect the competitiveness of goods.